Application of the UV-C photo-assisted peroxymonosulfate oxidation for the mineralization of dimethyl phthalate in aqueous solutions - Olmez-Hanci, Tugba; Imren, Ceren; Kabdaşlı, Işık; Tünay, Olcay; Arslan-Alaton, Idil (Springer Science and Business Media LLC, 2011)
In this study, the degradation of dimethyl phthalate (DMP), taken as model compound for phthalate esters, by the photo-assisted peroxymonosulfate (PMS) process was investigated. The high oxidation potential of hydroxyl and sulfate radicals generated by the activation of PMS under UV-C light irradiation was used to completely oxidize aqueous DMP solutions. Experiments were conducted at varying initial pH values (3.0, 6.0, and 9.0) and PMS concentrations (0-60 mM) to evaluate the effect of different reaction conditions on DMP treatment performance with the PMS/UV-C process. It was observed that lowering the initial reaction pH slightly improved the degradation rate of DMP. On the contrary, TOC abatements were slightly enhanced with increasing initial reaction pH. An adequate (optimum) PMS concentration of 40 mM resulted in the fastest and highest DMP degradation rates and efficiencies, respectively. At an initial concentration of 100 mg L(-1), more than 95% DMP removal was obtained after only 20 min under PMS/UV-C treatment conditions. For the proposed adequate PMS concentration (40 mM) the lowest electrical energy per order (EE/O) value was calculated as 2.9 kW h m(-3) order(-1).